2023
DOI: 10.1161/hypertensionaha.123.21274
|View full text |Cite
|
Sign up to set email alerts
|

Skin Cancer and Hydrochlorothiazide: Novel Population-Based Analyses Considering Personal Risk Factors Including Race/Ethnicity

Marina G. Birck,
Cristiano S. Moura,
Marina A.A. Machado
et al.

Abstract: BACKGROUND: Hydrochlorothiazide, a common antihypertensive, has photosensitive properties, potentially increasing skin cancer risk. We evaluated melanoma and nonmelanoma skin cancer among hydrochlorothiazide users with 3 different cohorts as each allows assessment of different potential cofounders/effect modifiers, including race/ethnicity. METHODS: We built 3 cohorts using IBM MarketScan Research Databases: commercial and encounters (>3.5 million in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…Although both commonly known and used drugs such as HCT and FUR are initially subjected to phototoxicity test, many new reports, systematic reviews, and cohort studies of phototoxic reactions have been reported as an adverse effects of pharmacotherapy with these drugs [14,[27][28][29]. Moreover, a lot of recent pharmacoepidemiological data have appeared to link a dose-dependent, cumulative association between long-term HCT treatment and increased risk of skin cancer [24,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both commonly known and used drugs such as HCT and FUR are initially subjected to phototoxicity test, many new reports, systematic reviews, and cohort studies of phototoxic reactions have been reported as an adverse effects of pharmacotherapy with these drugs [14,[27][28][29]. Moreover, a lot of recent pharmacoepidemiological data have appeared to link a dose-dependent, cumulative association between long-term HCT treatment and increased risk of skin cancer [24,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Although both commonly known and used drugs such as HCT and FUR are initially subjected to phototoxicity test, many new reports, systematic reviews, and cohort studies of phototoxic reactions have been reported as an adverse effects of pharmacotherapy with these drugs [14,[27][28][29]. Moreover, a lot of recent pharmacoepidemiological data have appeared to link a dose-dependent, cumulative association between long-term HCT treatment and increased risk of skin cancer [24,[27][28][29]. The meta-analyses of the relationship between pharmacotherapy with thiazide diuretics and the risk of skin cancer demonstrated an increased risk of developing non-melanoma skin cancers-squamous cell carcinoma (SCC) and basal cell carcinoma (BCC), for which the OR value was 1.86 and 1.19, respectively, and melanoma cancer (OR 1.14) [30].…”
Section: Discussionmentioning
confidence: 99%